Reflections on a decade of innovative research-for-development - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2022)
This synthesis brief captures insights and lessons from the implementation of the CGIAR Research Program on Water, Land and Ecosystems (WLE) over the past decade. By assessing the program’s performance, thematic scope and its management, governance and structure, as well as the ways in which the program has monitored and communicated its research outputs, this brief aims to consolidate WLE’s experiences and inform the transition to One CGIAR and the development of future research-for-development initiatives.